Seasonal variation in biomass yield and quality of Tithonia diversifolia at different cutting heights - Uu-Espens, Carol; Canul-Solís, Jorge R.; Chay-Canul, Alfonso J.; Piñeiro-Vázquez, Ángel T.; Villanueva-López, Gilberto; R. Aryal, Deb; Pozo-Leyva, Dixan; Casanova-Lugo, Fernando (Ecosistemas y Recursos Agropecuarios, 2022)
The objective of this research was to evaluate and compare the yield performance and quality of Tithonia diversifolia forage under different harvesting heights, during the dry and rainy seasons in tropical Mexico. The treatments consisted of three harvest heights 40, 60 and 80 cm from the ground level, cut every 60 days, during two seasons of the year. In each period, the biomass was harvested and separated into edible and non-edible components. We determined the biomass yield, and the concentration of crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF), lignin, ash and organic matter (OM) of the forage. Cutting at 80 cm height yielded the highest forage biomass per harvest (2 008 kg DM ha−1) while there were no significant differences in forage yield between 40 and 60 cm heights. The differences in cutting heights also affected the nutrient quality of the animal edible forage because the concentrations of CP, ADF and NDF varied significantly. There was a significant interaction between cutting heights and the season on forage production and quality. In the dry season, the content of NDF, FDA, lignin and ash were higher, while the PC and OM were lower. The use of T. diversifolia as a forage plant and cutting it to a height of 80 cm is recommended to maintain the best production and the quality of the forage throughout the year for livestock production.